For an anthropology of historians - Tran, Van; Noël, Patrick-Michel (Ethnologies, 2018)
The cliché is still lively: historians, as is well known, tend to portray themselves as craftsmen or artisans, mastering a practical know-how learned patiently through hands-on experience with dusty documents, and showing a conspicuous disdain towards theory and abstractions. This image deserves closer scrutiny. It is interesting that despite this insistence on the craftlike image of the profession, there seems to be a lack of ethnographic investigations of historians at work that would precisely pay attention to the craftiness of history and the multiple practicalities of doing history across different contexts. The idea that historians just do what they do sounds simple enough, but as is the case with any “craft,” from basket weaving to hunting in the rainforest, it is hardly self-evident, either technically or sociologically. To be sure, there are plenty of biographies, autobiographies, “ego-histories,” methodological primers and epistemological essays that tackle and debate the problems of the working historian, but these reflexive narratives remain essentially vertical. Taking our cue from some of the recent developments in science studies and the anthropology of science, we would like to propose in this article a program for a horizontal study of historians, that would be independent of their own reflexive discourse and symmetric in its explanations, and that would be attentive to the varieties of their existence and their becoming in a community of practice.